Financial irregularities and inadequate educational resources in Ghana: a case of secondary schools in Kwahu - Duah Daniel (knust, 2025)
A thesis submitted to the Department of Accounting and Finance, Kwame Nkrumah University of Science and Technology, School of Business in partial fulfilment for the award of Master of Science Degree in Accounting and Finance